2019
DOI: 10.1115/1.4042569
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Investigation of the Flow of Trailing Edge Cooling Slots

Abstract: Slot film cooling is a popular choice for trailing edge (TE) cooling in high pressure (HP) turbine blades because it can provide more uniform film coverage compared to discrete film cooling holes. The slot geometry consists of a cutback in the blade pressure side connected through rectangular openings to the internal coolant feed passage. The numerical simulation of this kind of film cooling flows is challenging due to the presence of flow interactions such as step flow separation, coolant-mainstream mixing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…for both aerodynamics and heat transfer applications [25,[35][36][37][38][39]. All the presented simulations are fully turbulent and steady, and wall functions are not used.…”
Section: Rans Methodsmentioning
confidence: 99%
“…for both aerodynamics and heat transfer applications [25,[35][36][37][38][39]. All the presented simulations are fully turbulent and steady, and wall functions are not used.…”
Section: Rans Methodsmentioning
confidence: 99%
“…IOP Publishing doi:10.1088/1742-6596/2772/1/012008 2 from the TEs were reported. Jiang et al [5] also used CFD approaches to investigate the flow of TE cooling slots. Their results revealed that the CFD approaches could reasonably predict the unsteady interaction between coolant and hot gas and vortex shedding at the slot lip.…”
mentioning
confidence: 99%